HTML5 and JavaScript projects - Meyer, Jeanine (Apress, 2011)
HTML5 and JavaScript Projects shows you how to build on your basic knowledge of HTML5 and JavaScript to create substantial HTML5 applications. Through the many interesting projects you can build in this book, you'll build your HTML5 skills for your future projects, and extend the core skills you may have learned with its companion book, The Essential Guide to HTML5. HTML5 and JavaScript Projects covers the most important areas of HTML5 that you'll want to know how to program, including: video, and audio, databases, localStorage, and geolocation. The projects have been carefully selected to help you build your HTML5 and JavaScript programming skills. You'll build games and applications, such as video jigsaws,  recipe archives, paper dolls, and many more captivating examples. Each project starts out with an introduction to the basic HTML5 and JavaScript concepts covered and then includes specific, appealing examples explained step-by-step. You'll also discover line-by-line explanations for every single line of code?we'll make sure that you can fully understand what each line of code does, so that you can easily take that understanding and apply it to your own HTML5 projects. HTML5 and JavaScript Projects: Shows how to produce applications combining Canvas drawings, photos, and videos Explains how to incorporate Google Maps and geolocation into your projects Reveals how to build applications requiring persistent data, storing the information locally or on a database on the ser